Pengaruh Sosial Ekonomi Keluarga Dan Strategi Penanggulangan Stunting Di Puskesmas Nurobo Kabupaten Malaka - Markus Uskunia; Nikson Tameno; Novi Theresia Kiak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to examine the influence of family socio-economic factors and coping strategies on editing at the Nurobo Community Health Center, Malaka Regency. This research uses a combined research approach (mixed methods). The sampling technique involves determining information using purposive sampling. The data analysis used in the quantitative method is validity testing, reliability testing, simple linear regression and hypothesis testing using that family socio-economic variables do not have a partial effect on the incidence of stunting with a coefficient of determination value of 0.4.5%. This aims to determine the Statistical Package tool for social science 28.0 for windows (SPSS). The data analysis used in the qualitative method is SWOT analysis. The test results show strategies for dealing with stunting incidents at the Nurobo Community Health Center. The results show that the most effective strategy can have a positive impact on stunting prevention strategies. Strategies that can be implemented to prevent stunting are by increasing access to better sanitation for the community and conducting educational outreach to make the community aware of the importance of nutritious food intake for toddlers to avoid stunting and other diseases in prevention efforts at the Nurobo Community Health Center, Malaka Regency.